Equiconvergence of some sequences of rational functions - M. A. Bokhari; A. Sharma (International Journal of Mathematics and Mathematical Sciences)
The phenomenon of equiconvergence was first observed by Walsh for two sequences of polynomial interpolants to a class of functions. Here we obtain analogues of Yuanren's results for Walsh equiconvergence using rational functions as in Saff and Sharma. We extend this to Hermite interpolation and an earlier result of [1] is improved and corrected.